Integrating Structural Support and Biological Regeneration in Male Stress Urinary Incontinence: A Conceptual Framework for the Translational Integration of Regenerative Medicine With Male Sling Surgery - Jianan Xu; Houdong He; Yihong Yao; Sheng Xu; Jihao Shen; Xiao Huang (Neurourology and Urodynamics, 2026)
ABSTRACT Background and Aims Male stress urinary incontinence (SUI), particularly post‐prostatectomy incontinence (PPI), remains a major functional complication. Artificial urinary sphincter implantation and male sling surgery improve continence mechanically but do not directly repair tissue injury. This review evaluates the rationale for a “structural support plus regenerative enhancement” strategy integrating sling surgery with regenerative medicine. Methods A narrative search of PubMed and Web of Science covered January 2002 to August 2026. Clinical and preclinical studies, reviews, guidelines, and consensus statements were considered. Results Direct clinical evidence for regenerative therapy in men is limited to uncontrolled studies of cell‐based interventions evaluated independently of sling surgery; cell‐free and carrier‐based approaches are supported mainly by preclinical or extrapolated evidence. No clinical study has evaluated regenerative therapy combined with male sling surgery. Accordingly, the combined approach remains a translational rather than an established treatment strategy. Selected patients with moderate PPI, partially preserved sphincter function, and sufficient residual tissue plasticity may be suitable for early investigation. Key uncertainties include delivery, durability, safety, manufacturing, regulation, and the need to distinguish biological repair from bulking or structural augmentation. Conclusions Regenerative medicine‐assisted male sling surgery remains a conceptual and investigational strategy. Controlled studies with standardized protocols and long‐term follow‐up are required to determine whether it provides a clinically meaningful benefit beyond sling surgery alone.